2023
DOI: 10.3390/agronomy13051256
|View full text |Cite
|
Sign up to set email alerts
|

Different Trap Types Depict Dissimilar Spatio-Temporal Distribution of Helicoverpa armigera (Hübner) (Lepidoptera: Noctuidae) in Cotton Fields

Abstract: Pheromone-baited traps have been widely used for the monitoring of the cotton bollworm, Helicoverpa armigera (Hübner) (Lepidoptera: Noctuidae), in order to time any control measures during the growing season. Different monitoring techniques may provide differential results regarding adult captures. However, studies on the comparative evaluation of the performance of different trap types on the captures of H. armigera are limited. To close this gap, in the present study, three different funnel traps (striped, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…In fact, location is a critical parameter and should be taken into account when a trap-based monitoring protocol is planned. For instance, Karakantza et al [39] reported high variation in the total captures of H. armigera adults among twenty cotton fields. The differences found among the traps that had been placed at different heights, although less pronounced as compared with those of the different trap types, were considerable during the second half of the monitoring period, when P. gossypiella adult numbers were high.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, location is a critical parameter and should be taken into account when a trap-based monitoring protocol is planned. For instance, Karakantza et al [39] reported high variation in the total captures of H. armigera adults among twenty cotton fields. The differences found among the traps that had been placed at different heights, although less pronounced as compared with those of the different trap types, were considerable during the second half of the monitoring period, when P. gossypiella adult numbers were high.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, UV light traps are found to be the most effective for CBW adult monitoring at low intensity for both sexes [38]. Some studies indicate that trap color influences CBW adult captures since they have a preference for bright colors [39].…”
Section: Introductionmentioning
confidence: 99%
“…According to our review, there is no rapid, cost-and labor-effective CBW damage surveillance method for maize, despite the high economic impact of the CBW. Satellitederived surface reflectance provides insights into the visual characteristics and changes in maize [47,55,56,70] that play an important role in determining the oviposition preferences of CBW adults under maize field conditions [13,30,[33][34][35][36][37][38][39]75]. Our hypothesis is that models, based on satellite imagery, can be developed, that will improve CBW surveillance (including both monitoring and prediction) for maize crops, aligned with an optimal time period and maize phenology.…”
Section: Introductionmentioning
confidence: 99%